The Validation of the Total Quality Management Construct Using Confirmatory Factor Analysis - Farooq Miiro (Interdisciplinary Journal of Education)
The empirical study sought to validate the structure of total quality management construct with an objective of identifying the current TQM practices employed as perceived by the staff of Islamic University in Uganda. A cross sectional survey was employed to solicit for data from 361 respondents. This was done through randomization and a confirmatory factor analysis of structural equation modelling technique which was employed for data analysis. The results are in congruent with the earlier findings whereby focus on clients, focus on satisfaction of the workers’ needs, process improvement, administrative and technological need were found as sound sub-dimensions of TQM. However, the research tool merged with only 20 items compared to the earlier tools used. The major implication is that enhancement of a survey tool with 21 items which other universities in future studies at the same level can be used to examine the levels of TQM practices at higher education institutions especially in Uganda. University managers and administrators can employ this tool often to examine how well they can reposition themselves in TQM practices. This kind of approach can lead to creation of a more impressing and interesting environment of teaching and learning and at the same time attract high quality personnel from both students and staff at international levels. The four subcontracts tool of TQM are imperative for universities to employ since the current times are more emphatic on customer demands and value for money.